(untitled) (Research, Society and Development, 2023)
Biological control is a growing branch in Brazil, and with it comes the need to obtain efficient enemies in the control of pests. The use of entomopathogens has expanded and with it comes the need to investigate their selectivity to non-target organisms. The present work was conducted in a pinecone (Annona squamosa L.) orchard with the objective of evaluating in which locations of the plant (lower, middle or upper third) and the effects of the entomopathogens: Beauveria bassiana, Metharhizium anisoplie and Bacillus thuringiensis on the predatory mite. Sixteen weekly applications were made between March and August 2017 with a constant pressure knapsack sprayer, nozzle type JA-2 with the jet directed at the entire plant. The treatments consisted of the use of three entomopathogenic biological products: Dipel, Beuaveria bassiana JCO and Metarhizium anisopliae JCO applied alone and in combination. Eight treatments were performed, as follows: T1-Spraying with M. anisopliae + phfos (Quimifol) + adhesive spreader (Agral), T2-Spraying with B. bassiana + phfos (Quimifol) + adhesive spreader (Agral), T3-Spraying with B. thruringiensis + phfos (Quimifol) + adhesive spreader (Agral), T4-Spraying with M. anisopliae + B. basisiana + phfos (Quimifol) + adhesive spreader (Agral), T5- Spraying with M. anisopliae + B. thruringiensis + phfos (Quimifol) + adhesive spreader (Agral), T6- Spraying with B. bassiana + B. thruringiensis + phfos (Quimifol) + adhesive spreader (Agral); T7- Spraying with M. anisopliae + B. bassiana + B. thruringiensis + phfos (Quimifol) + adhesive spreader (Agral) e T8-Testify, spraying with phfos (Quimifol) + adhesive spreader (Agral). The results indicate a preference of the Neoseiulus sp. mite for the middle third of the plant canopy. The results obtained indicated that the entomopathogens influenced the population of the Neoseiulus sp. mite until the sixth week after treatment, where the combination of Metarhizium anisopliae + Beauveria bassiana + Bacillus thuringiensis was the one that most negatively affected the population of the predatory mite Neoseiulus sp.